2008
DOI: 10.1002/masy.200851419
|View full text |Cite
|
Sign up to set email alerts
|

Particle Formation by Emulsion Inversion Method: Effect of the Stirring Speed on Inversion and Formation of Spherical Particles

Abstract: Summery: Phase inversion emulsification technique was employed in this work as a practical method to form epoxy particles. The effect of stirring speed on the inversion behaviour and the morphological aspects of the resulting solid epoxy particles are investigated. Emulsion inversion was induced by increasing the amount of initially dispersed deionized water in the presence of a non-ionic block copolymer surfactant at a fixed concentration. The process of inversion was followed by monitoring the variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thus, the disruptive forces generated by mixing at both speeds probably exceeded the cohesive forces. When stirring is energetic enough, the droplet and eddy scale is reduced, and translational Brownian motion of the emulsifier is high because surfactant diffusion from the bulk is partly substituted by convection, which enables rapid adsorption of the emulsifier at the oil-water interface [ 51 ]. High stirring speeds, however, also increase the likelihood of droplet coalescence by increasing droplet velocity and collision rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the disruptive forces generated by mixing at both speeds probably exceeded the cohesive forces. When stirring is energetic enough, the droplet and eddy scale is reduced, and translational Brownian motion of the emulsifier is high because surfactant diffusion from the bulk is partly substituted by convection, which enables rapid adsorption of the emulsifier at the oil-water interface [ 51 ]. High stirring speeds, however, also increase the likelihood of droplet coalescence by increasing droplet velocity and collision rate.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings indicate that increasing the homogenization speed is beneficial only when a critical speed is not exceeded, in agreement with previous findings regarding particle size and emulsion stability. Most studies have focused on simple emulsions with great variations in stirring speeds (e.g., 100–1300 rpm [ 51 ] and 10,000–15,000 rpm [ 54 ]) and emulsion composition. Liyana et al [ 54 ] found that the stability of O/W emulsions was improved by increasing the stirring speed from 10,000 to 15,000 rpm, but they did not measure particle size.…”
Section: Resultsmentioning
confidence: 99%
“…Fully spherical particles were formed above critical stirring speed. Further increase in the rotational speed of the mixer, significantly reduced the size of the spherical particles with a wide and random size distributions controlled and considerably narrowed by the stirring speed [19] . The result of the emulsion polymerization method has confirmed that increase in stirring speed from 100 to 500 rpm has significantly decreased the average particle size to around 700 nm and further increase in stirring speed in Fessi method from 500 to 1 000 rpm has reduced the average particle size below 100 nm which is mainly due to high shear rate [20] .…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by the minimization of the interfacial free energy usually resulting in spherical microparticles. 44 However, despite this challenge a variety of easily dissolvable anisotropic polymeric colloids have recently been prepared, including ellipsoids, 45 corpuscle-shaped, 46 and tetrahedral particles. 47 In most cases, anisotropic microparticles are fabricated by fine tailoring the colloidal procedure developed for spherical colloids.…”
Section: Anisotropic Organic Particlesmentioning
confidence: 99%